2020
DOI: 10.1042/bcj20200262
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI)-induced overactive mitophagy contributes to mitochondrial loss and cytotoxicity in L02 hepatocytes

Abstract: Hexavalent chromium [Cr(VI)] has aroused the main interest of environmental health researchers due to its high toxicity. Liver is the main target organ of Cr(VI), and the purpose of this study was to explore whether mitophagy contributes to Cr(VI)-induced hepatotoxicity and to demonstrate the potential mechanisms. Cr(VI) exposure induced mitochondrial loss, energy metabolism disorders and cell apoptosis, which were associated with the occurrence of excessive mitophagy characterized by the increased number of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A study showed that Cd could damage the structure and function of lysosomes, thereby blocking the autophagic flux to reduce autophagy in mouse neural crest-derived cells ( Pi et al, 2017 ). In turn, Cr(Ⅵ) was reported to induce excessive autophagy activation in mitochondria of hepatocytes, impairing their physiological activities ( Zhang et al, 2020c ). p62, as a selective autophagy substrate protein, is a critical factor regulating the step of substrate clearance, colocalizing with LC3B to enhance the autophagic flux ( Lamark et al, 2017 ), and being ultimately degraded in the middle and late stages of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that Cd could damage the structure and function of lysosomes, thereby blocking the autophagic flux to reduce autophagy in mouse neural crest-derived cells ( Pi et al, 2017 ). In turn, Cr(Ⅵ) was reported to induce excessive autophagy activation in mitochondria of hepatocytes, impairing their physiological activities ( Zhang et al, 2020c ). p62, as a selective autophagy substrate protein, is a critical factor regulating the step of substrate clearance, colocalizing with LC3B to enhance the autophagic flux ( Lamark et al, 2017 ), and being ultimately degraded in the middle and late stages of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, damaged mitochondria require elimination to maintain the cellular homeostasis, which is attained by mitophagy. Mitophagy, namely mitochondrial autophagy, is a targeted defense against mitochondrial impairment, playing critical roles in selective degradation of damaged or redundant mitochondria (Zhang et al, 2020b). There are two well-known routes for mitophagy: (1) the phosphatase and tensin homolog (PTEN) induced kinase I (PINK1)-Parkin pathway; and (2) the receptor (NIX/BNIP3L, BNIP3 and FUNDC1)-mediated pathway (Kubli and Gustafsson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanisms of reproductive toxicity caused by chromium include changes in sex hormone secretion, 14 oxidative stress, 15 and apoptosis 16 . In the recent years, autophagy and ferroptosis have been found to be the main mechanisms underlying the toxic effects of heavy metals 17–20 . Autophagy plays an important role in cell survival and maintenance by degrading and recycling cellular components and products 21 .…”
Section: Introductionmentioning
confidence: 99%
“…21 However, autophagy can be a double-edged sword: it can protect cells from death, but excessive autophagy can damage healthy cells. [22][23][24][25] Zhang et al 20 reported that in an in vitro test of L-02 hepatocytes, excessive mitophagy played an important role in Cr(VI)induced mitochondrial loss and cell death. Our previous work also demonstrated that excessive Cr(VI)-induced autophagy caused kidney damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation